Electrical stimulation of the superior colliculus induces non-topographically organized perturbation of reaching movements in cats - Courjon, Jean-Hubert; Zénon, Alexandre; Clément, Gilles; Urquizar, Christian; Olivier, Etienne; Pélisson, Denis (Frontiers in Systems Neuroscience, 2015)
Besides its well-known contribution to orienting behaviors, the superior colliculus (SC) might also play a role in controlling visually-guided reaching movements. This view has been inferred from studies in monkeys showing that some tectal cells located in the deep layers are active prior to reaching movements; it was corroborated by functional imaging studies performed in humans. Likewise, our group has already demonstrated that, in cats, that SC electrical stimulation can modify the trajectory of goal-directed forelimb movements without necessarily affecting the gaze position. However, as in monkeys, we could not establish any congruence between the usual retinotopic SC map and direction of evoked forelimb movements, albeit only a small portion of the collicular map was investigated. Therefore, the aim of the current study was to further ascertain the causal contribution of SC to reaching movement by exploring the whole collicular map. Our results confirmed that SC electrical stimulation deflected the trajectory of reaching movements, but this deviation was always directed downward and backward, irrespective of the location of the stimulation site. The lack of a complete map of reach directions in the SC and the absence of congruence between the direction of evoked forelimb movements and the collicular oculomotor map challenge the view that, in the cat, the SC causally contributes to coding forelimb movements. Interestingly, the very short latencies of the effect argue also against the interruption of reaching movements being driven by a disruption of the early visual processing. Our results rather suggest that the SC might contribute to the reach target selection process. Alternatively, SC stimulation might have triggered a postural adjustment anticipating an upcoming orienting reaction, leading to an interruption of the on-going reaching movement.